Cover Feature: Frontiers in Hybrid Ion Capacitors: A Review on Advanced Materials and Emerging Devices (ChemElectroChem 8/2021). Issue 8 (22nd March 2021) - Naskar, Pappu; Kundu, Debojyoti; Maiti, Apurba; Chakraborty, Priyanka; Biswas, Biplab; Banerjee, Anjan
Abstract : The Cover Feature depicts the coupling of two electrochemical energy storage systems (i. e. a battery and a supercapacitor) with different characteristics, just like cooperation between two people. The hybrid system features optimized energy and power densities, and it could be employed in a diverse range of applications, such as renewable energy storage, electrification of vehicles, and so forth. More information can be found in the Review by A. Banerjee & co‐workers .